Strategy Development for Community Elevation to Creative Tourism of Ban Phu Nam Ron, Dan Chang District, Suphan Buri Province - Lamviriyawat, Patarporn; Khamsa-Ard, Santhipharp (Dusit Thani College Journal, 2020)
This research aims to study basic information and potential of creative tourism resources of Ban Phu Nam Ron community, Dan Chang District, Suphanburi Province and draft of strategic proposal to raise the level of community’s creative tourism to present and certify the strategy in order to raise the community to creative tourism of Ban Phu Nam Ron community by using qualitative and quantitative research methods and participatory observation In-depth interview also, the draft of strategic proposals with the EDFR (Ethnographic Delphi Futures Research) future research technique. The main informants in the research are 3 groups of community representatives, government officials who directly involved, and quality tourist groups who have experience, knowledge and understanding in community tourism by organizing a meeting to certify policy proposals in order to know the problems, hurdles, trends and elements in drafting proposals for strategies to enhance the community into creative tourism management of Ban Phu Nam Ron community. The research found that the community has the identity of the “Lao Khrang” ethnic group, being well equipped with natural resources, traditions and culture, suitable for tourism management, community, potential, and ready to be able to raise the level of community tourism into creative tourism also, the development of strategies to raise the community to creative tourism that lead into cooperation of tourism management to gains benefits to Ban Phu Nam Ron community in all aspects such as economy, environment, society and culture. The strategic plan consisting of 4 strategic issues that are 1) creating patterns from economic development and economic wisdom to add value and value from the community identity base to creative tourism 2) Develop marketing strategies to create tourists’ awareness of the community in creative tourism. 3) Tourism links between communities and networks to increase the duration of stay through the upgrading of tourism activities 4) Personnel knowledge development in the community and support participation in creative tourism development